Race, wrongs, and remedies : group justice in the 21st century - Wax, Amy (Amy L.) (Hoover studies in politics, economics, and society., 2009)
Black Americans continue to lag behind on many measures of social and economic well-being. Conventional wisdom holds that these inequalities can only be eliminated by eradicating racism and providing well-funded social programs. In Race, Wrongs, and Remedies, Amy L. Wax applies concepts from the law of remedies to show that the conventional wisdom is mistaken. She argues that effectively addressing today's persistent racial disparities requires dispelling the confusion surrounding blacks' own role in achieving equality. The evidence overwhelmingly suggests that discrimination against blacks h.